2007
DOI: 10.1007/s00436-007-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Camallanus cotti in greatly diverse fish species from Danjiangkou Reservoir in central China

Abstract: Two thousand four hundred fifty-eight fish comprised of 53 species were captured in the Danjiangkou Reservoir, in the northwestern part of Hubei Province, central China during 2004, to examine Camallanus cotti infections. We found that 19 cypriniform, 3 siluriforme, and 4 perciforme fishes were infected by the nematode. Our study revealed the species, Hemiculter bleekeri bleekeri, Culter oxycephaloide, Pseudolaubuca sinensis, Acanthobrama simony, Mylopharyngodon piceus, Ctenopharyngodon idella, Gnathopogon imb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…While non-native tropical fishes like A. nigrofasciata are not likely to persist in colder stream regions, C. cotti is known to be a generalist parasite, using a wide range of fish hosts and to be able to survive successfully at lower temperatures (Wu et al 2007). Especially perches (Perca fluviatilis), sticklebacks (G. aculeatus), and eels (A. anguilla) could be susceptible to C. cotti, as they are common hosts for the native, closely related C. lacustris (Moravec 2013).…”
Section: Parasite Fauna Of a Nigrofasciatamentioning
confidence: 99%
See 1 more Smart Citation
“…While non-native tropical fishes like A. nigrofasciata are not likely to persist in colder stream regions, C. cotti is known to be a generalist parasite, using a wide range of fish hosts and to be able to survive successfully at lower temperatures (Wu et al 2007). Especially perches (Perca fluviatilis), sticklebacks (G. aculeatus), and eels (A. anguilla) could be susceptible to C. cotti, as they are common hosts for the native, closely related C. lacustris (Moravec 2013).…”
Section: Parasite Fauna Of a Nigrofasciatamentioning
confidence: 99%
“…Especially perches (Perca fluviatilis), sticklebacks (G. aculeatus), and eels (A. anguilla) could be susceptible to C. cotti, as they are common hosts for the native, closely related C. lacustris (Moravec 2013). Cyprinid fishes are commonly infected by C. cotti in Asia (Wu et al 2007), and different cyprinid species are also abundant in the Gillbach and adjacent rivers, such as the Erft and Rhine. Cyprinids could, therefore, act as intermediate hosts for the generalist parasite, spreading the parasite beyond the Gillbach.…”
Section: Parasite Fauna Of a Nigrofasciatamentioning
confidence: 99%
“…The threshold of 1.7% was established using as standard the difference between valid species in the genus. Recently, research on 9 species of philometrids collected in China revealed that the interspecific divergence was more than 7.32% in the ITS region (Wu et al, 2005). All these studies, and many others, indicated that for parasitic nematodes, there was a significant difference between the variations of intra-and interspecies whether the ITS1, ITS2, or combined rDNA sequences were used.…”
Section: Species Validity Within Camallanus Sppmentioning
confidence: 99%
“…As a generalist parasite, it is frequently found in many species of the Cypriniformes, Siluriformes, and Perciformes. Recent surveys of helminths reveal that the host range and geographic distribution of this species are increasing and that the worm is a potential danger to endemic fishes (Font and Tate, 1994;Wu et al, 2007). Of the remaining species, C. hypophthalmichthys is a relative specialist, recorded in only 2 species of fish in the Hypophthalmichthyinae, whereas C. zacconis shares some hosts with C. cotti.…”
mentioning
confidence: 99%
“…Whereas C. corderoi, a parasite mainly of P. trucha in Chile and Argentina, has the buccal capsule with dentigerous ridges (subgenus Zeylanema Yeh), both other species, parasites of osteoglossiform fishes in the Amazon River Basin, have smooth ridges in the capsule (nominotypical subgenus Camallanus); the latter differ from each other in conspicuously different lengths and shapes of the female tail. Recently, Martins et al (2007) described a new species, C. maculatus Martins, Garcia, Piazza and Ghiraldelli from the cultured ornamental fish Xiphophorus maculatus (Günther) in Brazil, but this is evidently a synonym of C. cotti, an Asian species now introduced into many countries of different continents, where it parasitizes many species of cultured and native fish species , Wu et al 2007). suggested this synonymy, but because the paper describing C. maculatus was not yet published at that time, they could not do it formally.…”
Section: Tridentatus Was Described Bymentioning
confidence: 99%